Standard setting and competition in securities settlement - Alistair Milne (Bank of Finland, 2005)
This paper examines the impact of messaging and technical standards on competition in the supply of securities transaction management services. Two simple switching cost models are used to clarify the impact of standards on barriers to entry and on the incentives to adopt harmonised and simplified securities processing standards. Policy implications are discussed briefly.
URN:NBN:fi:bof-201501291024
Keywords: L15; L86; 330; securities settlement; standards; inter-operability; switching costs